Controlled and localized antibiotics delivery using magnetic‐responsive beads for synergistic treatment of orthopedic infection. Issue 5 (8th January 2022) - Shademani, Ali; Jackson, John K.; Thompson, Charles J.; Chiao, Mu
Abstract: Antibiotic‐loaded bone cement beads have been a reliable passive delivery system for the localized treatment of osteomyelitis; however, low, and unregulated drug release rates limit the ability of this system to maintain therapeutic concentrations. This problem is further amplified by drug‐resistant pathogens that might invade or evolve under these conditions. Furthermore, currently available bone cements are incompatible with some antibiotics. The proposed device resembles conventional bone cement beads but contains an on‐demand drug delivery magnetic sponge that provides actively controlled release of antibiotics. The slightly porous structure facilitates some drug diffusion while further drug release may be controlled remotely via magnetic actuation. Additionally, a combination of silver nitrate and gentamicin are used in the device as these agents are shown to display a synergistic antibacterial activity in vitro using checkerboard and time‐kill assays. The device releases gentamicin and silver in both actuation and diffusion modes over 7 days. The in vitro bacterial studies demonstrate the efficacy of the released agents alone, and synergistically in combination, against Methicillin‐resistant Staphylococcus aureus and Escherichia coli . The proposed device offers a facile fabrication process which allows control of the release profile by engineering hole configurations or manipulating magnetic field strength to provide the most effective therapy.